THE INFLUENCE OF PATIENT SAFETY ON NURSE PERFORMANCE AT SANTA FAMILIA HOSPITAL - Natalis Hurang, Christianus; Nurhasanah, Nurhasanah; Mardahlia, Dewi (Proceeding of International Conference on Multidisciplinary Research, 2024)
Patient Safety was a system aimed at making patient care safer. The goal of Patient Safety was to advance specific improvements in patient safety. The objective was to determine the influence of patient safety on nurse performance. The method used was quantitative with a cross-sectional design. The population size was 50 individuals, with a minimum sample of 23 nurses at Santa Familia Hospital, selected using a simple random sampling technique. The research instrument utilized a questionnaire. Data analysis techniques included descriptive statistics, validity, reliability, classical assumption tests, linear regression tests, F-tests, and determination coefficients. Results showed that out of 27 respondents, the majority were female (96%), aged between 26-35 years (44%), had a Diploma III in Nursing (92%), and had been working for 1-2 years (52%). Patient Safety at Santa Familia Hospital was categorized as high (85.2%), while nurse performance was categorized as moderate (51.9%). Statistical tests revealed no significant influence between patient safety (p-value = 0.267>0.05) and nurse performance at Santa Familia Hospital. However, results showed significant impacts of 6 patient safety targets on nurse performance at Santa Familia Hospital: target 1 (t-value = 2.623>2.060, p-value = 0.016), target 2 (p-value = 0.584), target 3 (p-value = 0.805), target 4 (t-value = (-5.606)>2.060, p-value=0.000), target 5 (p-value = 0.360), and target 6 (p-value=0.698). This research concluded that there was no significant influence of patient safety on nurse performance at Santa Familia Hospital. However, there was a positive impact of patient identification accuracy (target 1) and a negative impact of surgical site, procedure, and patient accuracy (target 4) on nurse performance at Santa Familia Hospital. Recommendations include further investigation into factors causing high patient safety but low performance.